Leading and managing in nursing - Yoder-Wise, Patricia S. (Elsevier, 2019)
Help students prepare for the NCLEX® and their transition to practice! Organized around the issues in today's constantly changing healthcare environment Leading and Managing in Nursing, 7th Edition, offers an innovative approach to leading and managing by merging theory, research, and practical application. This cutting-edge text includes coverage of patient safety, consumer relationships, cultural diversity, resource management delegation, and communication. In addition, it provides just the right amount of information to equip students with the tools they need to master leadership and management, which will better prepare them for clinical practice.